The Effect of Rutin on some of the Cardiac Biomarkers in White Male Rats Exposed to Oxidative Stress - Muhammad Fadhel Al Hussani, Aseel Najah Sabour (Pakistan Journal of Medical & Health Sciences, 2022)
The current study was designed to investigate the effect of Rutin on some physiological parameters related to the heart in male white rats exposed to oxidative stress with hydrogen peroxide. The study included 48 adult male white rats, their weights ranged from (220-280) g, and their ages ranged between (8-12) weeks. The rats were randomly distributed into six groups of 8 rats for each group, and as follows: The first group, group 1, was considered a negative control group G1 that was supplied with water and the diet for the duration of the experiment which amounted to 30 days and the second group, group 2, was considered a positive control group that was given drinking water containing hydrogen peroxide at a concentration of 1% by means of special drinking bottles and the diet for 30 days, the third group G3 was orally dosed with Rutin at a concentration of 60 mg/kg of body weight in addition to drinking water containing hydrogen peroxide at a concentration of 1% for 30 days . The fourth group G4 also dosed orally with a solution of Rutin at a concentration of 30 mg/kg bw in addition to drinking water containing hydrogen peroxide at a concentration of 1% for 30 days. fifth group G5 dosed orally with a Rutin only at a concentration of 30 mg / kg bw for 30 days. the sixth group G6 was also dosed orally with Rutin only at a concentration of 30 mg / kg bw for30 days. After the end of the experiment, the animals were anesthetized then blood was drawn from the heart directly for the purpose of obtaining serum to measure the level of Troponin, LDH, CK-MB and Myoglobin. The results showed a significant increase (p < 0.05) in the level of Troponin, LDH and Ck-MB in the positive group compared to the negative control group, while a significant decrease in the levels of these enzymes was observed in the third and fourth groups compared to the positive control group, while in the two groups The fifth and sixth recorded a significant decrease compared to the positive control group. After obtaining these results, it became clear that Rutin compound has a positive effect in preventing oxidative stress and heart muscle damage. Keywords: Rutin, hydrogen peroxide, Rats.